Therapeutic Effect of Astragalus Polysaccharides on Hepatocellular Carcinoma H22-Bearing Mice - Xiaoyu Lai; Weibiao Xia; Jing Wei; Xinghong Ding (SAGE Publishing, 2017)
The purpose of this study was to investigate the effect of astragalus polysaccharides (APSs), active constituents of astragalus, in the treatment of hepatocellular carcinoma (HCC) and their potential as a promising candidate for future anticancer drug development. Astragalus polysaccharide was administered at different doses to HCC H22-bearing mice to investigate their antitumor effects. Results revealed that APS inhibited the growth of H22 cells with a tumor inhibition rate in the APS 400 mg·kg −1 group of 59.01%. Astragalus polysaccharides significantly increased the spleen and thymus indexes, and also the interleukin (IL) 2, IL-6, and tumor necrosis factor α cytokine concentration in serum, indicating that APS influences immune-regulating properties involved in antitumor activity. In addition, APS increased Bax protein expression and decreased Bcl-2 protein expression; these proteins are apoptosis-regulating factors responsible for cell death or survival. Further development and exploration of APS may enable it to become an effective clinical agent for liver cancer therapy.